Relevansi Konsep Kurikulum Pendidikan Islam Menurut Imam Al-Ghazali Pada Masa Sekarang Khususnya di Indonesia - Hasanah, Uswatun, Istanto, S.Pd.I, M.Pd (2017)
Background this study was the importance of the role and function of the curriculum in the education system, because the curriculum is an important tool in the realization of educational programs both formal and non formal, so that the description of the educational system can be seen clearly in the curriculum. Imam Al-ghazali was a prominent Islamic thought and one of the educators who are experts in his workin the field of education especially at of one of his works titled "Ihya ' Ulumiddin". According to the paper in the concept of Islamic education Imam Al-ghazali includeseducational objectives, curricula, learning methods and assessment or evaluation ofbelajara related to science. The matter will be investigated is how the concept of curriculum of Imam Alghazaliand whether it is still relevant to the current curriculum. This research aims to know and describe the Islamic education curriculum according to Imam Al-Ghazali and to know the relevance of the concept of Islamic education curriculum according to Imam Al-Ghazali in the present. This research is a research library (library reseacrh), with the collection of data is done using the dokumntasi method, namely through the objects written in the form ofbooks, documents and the internet that can support research studies. Data analysisconducted with the model analysis of the content (content analysis). The results showed: (1) the concept of Islamic education curriculum according to Imam Al-ghazali in Ihya ' Ulumiddin book was that for he Islamic education curriculum are classified into two parts, the first mandatory curriculum or ijbari curriculum and the second ikhtiary curriculum or curriculum is not necessary/option. (2) at the time of sekarangini in the middle of the morality of human yangturun education offered by Imam Al-ghazali is highly relevant to the latest curriculum concept in Indonesia namely curriculum 2013. Noble morals and rel igious education is very important in the middle of our society now because of this breathtaking expected moral society be good again by applying a conditioning against good curriculum Ijbari manupun Ikhtiyari in kuriklu m 2013.